Visual lectures for dyslexic students - David Roberts (2018)
Lecturing in Higher Education is dominated by PowerPoint presentations characterised by text and bullet points. But research tells us this is harmful because it overloads our minds’ ability to process text whilst simultaneously under-exploiting our ability to comprehend through imagery. It’s bad enough for neurostandard students, but for dyslexic students it can often be far worse. This chapter presents an alternative way of using PowerPoint that inverts how we use it so it takes advantage of visual processing abilities and presents text in cognitively-digestible ways. The method privileges very large, high-quality images not as supplements but as the means to convey substance and meaning. The chapter presents a range of evidence that reveals especially how dyslexic students benefit from using images effectively, but the message applies to many student cohorts in various disciplines because it’s cognitive, not disciplinary. The chapter concludes with demonstrations and advice on finding copyright-appropriate images